Cardiovascular Risk Behavior Amongst Adolescents of Lekhnath Muncipality of Kaski district, Nepal - Ghimire, H P; Dhungana, A (Journal of Gandaki Medical College-Nepal, 2018)
Background: Life style related behavioral risk factors are mainly implicated for increase burden of cardiovascular diseases. Research related to these risk behaviors especially among adolescents is essential considering their role as future citizens of the country.Objectives: The study aimed to evaluate the burden of cardiovascular risk behavior amongst the adolescents of Kaski district, Lekhnath Nepal.Methods: A cross sectional study was carried out among the adolescents of Lekhnath Muncipality Kaski District. Total 350 participants from five different schools from Lekhnath Muncipality took part in the study and the sampling technique was simple random method by using a random number table. Self administered questionnaires were used to collect information on identification of risk behaviors.Results: Descriptive statistics and Chi square test were computed. Out of 350 adolescents 175 males and remaining 175 females were interviewed. Alcohol and tobacco consumption were more amongst males whereas fast food and soft drinks were more amongst the females. Nearly 40% of the adolescents were not involved in physical activity. Tobacco and alcohol consumption was 26% and 16% respectively, which was higher amongst the late adolescents group studying in the 11th and 12th standard. In this study fruits and vegetables consumption was very less only 42% whereas soft drinks and fast food consumption was more 83% which shows that the adolescents are not aware about their food habits. Some participants did not consume fruits due to low purchasing power to buy fruits. Adolescence is a period of experimentation and so some participants told that they have just started taking alcohol and also started consuming tobacco for fun and were not aware that it was cardiovascular risk behavior.Conclusions: The adolescents had a high burden of cardiovascular risk behavior and if immediate intervention is not done to reduce these high risk behaviors many may be vulnerable to cardio vascular diseases in the future. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 10-13